THE THE EFFECT OF GREEN MENIRAN EXTRACT ON AVIAN INFLUENZA ANTIBODY TITER IN BROILERS TWO WEEKS BEFORE VACCINATION - Dewandaru Evan Wintyassatya; Ida Bagus Kade Suardana; Romy Muhammad Dary Mufa; I Made Sukada; Ni Luh Eka Setiasih; I Made Kardena (Buletin Veteriner Udayana, 2025)
Avian Influenza (AI) is a viral disease that poses a serious threat to poultry farming, particularly in broiler production. The rapid and massive spread of AI in poultry flocks can cause substantial economic losses for farmers. Vaccination is one of the primary strategies for AI prevention; however, the currently available AI vaccines are killed/inactivated types, which tend to induce antibody titers slowly. This limitation, coupled with the relatively short rearing period of broilers, reduces vaccine effectiveness in broiler chickens. This study aimed to evaluate the effect of green meniran (Phyllanthus niruri Linn.) extract on enhancing antibody titers in broilers when administered for two weeks prior to AI vaccination. A total of 30 broiler chickens aged from day 1 to 32 days were used as experimental subjects. The study employed a Completely Randomized Design (CRD) with three groups: negative control (K−), positive control (K+), and treatment group (P). Data were analyzed using Analysis of Variance (ANOVA) and Regression Analysis via SPSS software. The results demonstrated a comparative increase in average antibody titers in the treatment group receiving Phyllanthus niruri extract compared to the control groups. It was concluded that supplementation with Phyllanthus niruri extract effectively enhanced antibody titers in broilers vaccinated with the inactivated AI La Sota vaccine, with peak antibody responses observed 1–2 weeks post-vaccination. The administration of green Phyllanthus niruri extract has been proven to stimulate antibody titers in broilers by accelerating the development of protective antibody levels against the AI virus. The timing of sample collection was shown to significantly affect antibody titers, with the highest levels observed during the first to second week post-vaccination. Future research on the administration of Phyllanthus niruri extract to improve antibody titers against Avian Influenza (AI) in broilers is expected to extend the duration of supplementation until the harvesting period and to include higher dosage variations in order to achieve more optimal and protective results.